The Roles of VHL-Dependent Ubiquitination in Signaling and Cancer - Zhang, Qing; Yang, Haifeng (Frontiers in Oncology, 2012)
The function of tumor suppressor VHL is compromised in the vast majority of clear cell Renal Cell Carcinoma (ccRCC), and its mutations or loss of expression was causal for this disease. pVHL was found to be a substrate recognition subunit of an E3 ubiquitin ligase, and most of the tumor-derived mutations disrupt this function. pVHL was found to bind to the alpha subunits of hypoxia inducible factor (HIF) and promote their ubiquitination and proteasomal degradation. Proline hydroxylation on key sites of HIFα provides the binding signal for pVHL E3 ligase complex. Beside HIFα, several other VHL targets have been identified, including activated Epidermal Growth Factor Receptor (EGFR), RNA polymerase II subunits RPB1 and hsRPB7, atypical PKC, Sprouty 2, β-adrenergic receptor II and Myb-binding protein p160. HIFα is the most well studied substrate and has been proven to be critical for pVHL's tumor suppressor function, but the activated EGFR and PKC and other pVHL substrates might also be important for tumor growth and drug response. Their regulations by pVHL and their relevance to signaling and cancer are discussed.